1999
DOI: 10.2337/diabetes.48.9.1747
|View full text |Cite
|
Sign up to set email alerts
|

Glucose-fatty acid cycle to inhibit glucose utilization and oxidation is not operative in fatty acid-cultured islets.

Abstract: The glucose-fatty acid cycle of Randle entails two elements: decreased pyruvate dehydrogenase (PDH) activity, which inhibits glucose oxidation, and inhibition of phosphofructokinase (PFK) by a rise in citrate so that glucose-6-phosphate (G-6-P) levels increase, thereby inhibiting hexokinase activity and hence glucose utilization. Chronic exposure of islets to long-chain fatty acids (FA) is reported to lower PDH activity, but the effect on glucose oxidation and glucose-induced insulin secretion is uncertain. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
56
0
2

Year Published

2000
2000
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(66 citation statements)
references
References 40 publications
8
56
0
2
Order By: Relevance
“…We studied ␤-cells exposed to states of excess fatty acids in which glucose-induced insulin secretion is preserved, and we have identified another potential regulatory role for PC and its downstream pathways. We cultured islets for 4 days with 0.25 mmol/liter oleate and 5.5 mmol/liter glucose, and we observed that glucose oxidation was increased despite pyruvate dehydrogenase (PDH) activity being lowered by 30% (17). We made a similar finding in isolated islets from insulin-resistant, hyperlipidemic, nondiabetic Zucker fatty rats (18).…”
supporting
confidence: 56%
See 4 more Smart Citations
“…We studied ␤-cells exposed to states of excess fatty acids in which glucose-induced insulin secretion is preserved, and we have identified another potential regulatory role for PC and its downstream pathways. We cultured islets for 4 days with 0.25 mmol/liter oleate and 5.5 mmol/liter glucose, and we observed that glucose oxidation was increased despite pyruvate dehydrogenase (PDH) activity being lowered by 30% (17). We made a similar finding in isolated islets from insulin-resistant, hyperlipidemic, nondiabetic Zucker fatty rats (18).…”
supporting
confidence: 56%
“…Islets are more complex because of the presence and high activity of PC (22). In our studies of fatty acid-associated lowering of PDH activity (17,18), PC activity was unaffected or slightly increased, and flux through the malate-pyruvate shuttle was more than doubled, as was the concentration of pyruvate. We proposed from these findings that islets are protected against the mitochondrial dysmetabolism that occurs with excess fatty acids in other tissues because of having an alternate pyruvate metabolism pathway through PC and that diversion through this pathway results in augmented flux through the pyruvate shuttles, which raises the level of cytoplasmic pyruvate to an extent that overcomes the lowered PDH activity through mass action.…”
mentioning
confidence: 77%
See 3 more Smart Citations